The Influence of Sales Promotion and Hedonic Shopping Motivation on Impulse Buying with Positive Emotion as an Intervening Variable on E-Commerce Customers In Indonesia - Ni Luh Aria Sukma Dewi; Ni Luh Putu Indiani; Ni Made Wahyuni (PT Keberlanjutan Strategis Indonesia, 2026)
The development of e-commerce in Indonesia has increased quite rapidly. E-commerce has become an important part of people's lives today because more and more people choose to shop online. The emergence of impulse buying consists of external factors, namely sales promotion and internal factors, namely hedonic shopping motivation . The positive emotion variable was chosen as a mediating variable to reflect how much public enthusiasm is related to positive emotions which cause customers to impulse buy . The variables sales promotion, hedonic shopping motivation are thought to be significant in influencing impulse buying among e-commerce customers with positive emotion as an intervening variable. The aim of this research is to analyze the influence of sales promotion and hedonic shopping motivation on impulse buying with positive emotion as an intervening variable for e-commerce customers . The method used in this research is quantitative with a questionnaire carried out systematically in accordance with the research objectives. The population in this study were Indonesian people who had used e-commerce for online shopping with 120 respondents. This research uses 5 Likert scales to measure variables when testing the validity and reliability of variables. This research was analyzed using PLS-based SEM. The research results show that (1) Sales promotion significant effect on impulse buying . (2) Hedonic shopping motivation has a significant positive effect on impulse buying. (3) Sales promotion positive influence on positive emotions.